Cost-effectiveness of liver transplantation in patients with colorectal metastases confined to the liver. Issue 1 (16th October 2018) - Bjørnelv, G M W; Dueland, S; Line, P-D; Joranger, P; Fretland, Å A; Edwin, B; Sørbye, H; Aas, E
Abstract: Background: Patients with non-resectable colorectal metastases are currently treated with chemotherapy. However, liver transplantation can increase the 5-year survival rate from 9 to 56 per cent if the cancer is confined to the liver. The aim of this study was to estimate the cost-effectiveness of liver transplantation for colorectal liver metastases. Methods: A Markov model with a lifetime perspective was developed to estimate the life-years, quality-adjusted life-years (QALYs), direct healthcare costs and cost-effectiveness for patients with non-resectable colorectal liver metastases who received liver transplantation or chemotherapy alone. Results: In non-selected cohorts, liver transplantation increased patients' life expectancy by 3·12 life-years (2·47 QALYs), at an additional cost of €209 143, giving an incremental cost-effectiveness ratio (ICER) of €67 140 per life-year (€84 667 per QALY) gained. In selected cohorts (selection based on tumour diameter, time since primary cancer, carcinoembryonic antigen levels and response to chemotherapy), the effect of liver transplantation increased to 4·23 life-years (3·41 QALYs), at a higher additional cost (€230 282), and the ICER decreased to €54 467 per life-year (€67 509 per QALY) gained. Given a willingness to pay of €70 500, the likelihood of transplantation being cost-effective was 0·66 and 0·94 (0·23 and 0·67 QALYs) for non-selected and selected cohorts respectively. Conclusion: Liver transplantation was cost-effective but only for highly selected patients. This might be possible in countries with good access to grafts and low waiting list mortality. Abstract : Not cost effective for everyone